Pengaruh Perceived Ease of Use, Perceived Usefulness, Price Perception Terhadap Repurchase Intention Melalui Service Quality, Trust Sebagai Variabel Intervening Konsumen Yang Memanfaatkan Erigo Store Pada Aplikasi TikTok Shop - Finarizal Munthaha; Vivina Eprillison; Hayu Yolanda Utami (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
This study to determine (1) the effect perceived ease of use,perceived usefulness, and price perception on service quality (2) the effect perceived ease of use, perceived usefulness, price perception and service quality on trust (3) the effect perceived ease of use, perceived usefulness, price perception, service quality, and trust on repurchase intention.This type of research is associative research.The population in this study are consumers who purchase products from the Erigo Store through the TikTok Shop application.A sample of 120 people with a sampling technique in the form of random sampling.The research instrument used in this study was a closed questionnaire with path analysis testing.The data analysis technique used is descriptive analysis technique and inductive analysis, with the help of the SPSS version 29 program.The results of this study indicate that: (1)perceived ease of useand perceived usefulness have a positive and significant effect on service quality(2)price perception has no significant effect on service quality(3)perceived usefulness and service quality have a positive and significant on trust(4)perceived ease of use and price perception have no significant on trust(5)price perception and trust have a positive and significant on repurchase intention(6)perceived ease of use, perceived usefulness, and service quality have no significant on repurchase intention.